Dolabelladienetriol, a compound from Dictyota pfaffii algae, inhibits the infection by Leishmania amazonensis. - Deivid Costa Soares; Teresa C Calegari-Silva; Ulisses G Lopes; Valéria L Teixeira; Izabel C N de Palmer Paixão; Claudio Cirne-Santos; Dumith Chequer Bou-Habib; Elvira M Saraiva (Public Library of Science (PLoS), 2012)
BACKGROUND: Chemotherapy for leishmaniasis, a disease caused by Leishmania parasites, is expensive and causes side effects. Furthermore, parasite resistance constitutes an increasing problem, and new drugs against this disease are needed. In this study, we examine the effect of the compound 8,10,18-trihydroxy-2,6-dolabelladiene (Dolabelladienetriol), on Leishmania growth in macrophages. The ability of this compound to modulate macrophage function is also described. METHODOLOGY/PRINCIPAL FINDINGS: Leishmania-infected macrophages were treated with Dolabelladienetriol, and parasite growth was measured using an infectivity index. Nitric oxide (NO), TNF-α and TGF-β production were assayed in macrophages using specific assays. NF-kB nuclear translocation was analyzed by western blot. Dolabelladienetriol inhibited Leishmania in a dose-dependent manner; the IC(50) was 44 µM. Dolabelladienetriol diminished NO, TNF-α and TGF-β production in uninfected and Leishmania-infected macrophages and reduced NF-kB nuclear translocation. Dolabelladienetriol inhibited Leishmania infection even when the parasite growth was exacerbated by either IL-10 or TGF-β. In addition, Dolabelladienetriol inhibited Leishmania growth in HIV-1-co-infected human macrophages. CONCLUSION: Our results indicate that Dolabelladienetriol significantly inhibits Leishmania in macrophages even in the presence of factors that exacerbate parasite growth, such as IL-10, TGF-β and HIV-1 co-infection. Our results suggest that Dolabelladienetriol is a promising candidate for future studies regarding treatment of leishmaniasis, associated or not with HIV-1 infection.